Dampak Sampah Anorganik terhadap Vegetasi Mangrove Tingkat Semai di Ekosistem Mangrove Wonorejo Surabaya - Sherlin Fatwa Fatmalah; Nor Sa'adah; Nirmalasari Idha Wijaya (Universitas Hang Tuah, 2022)
The Wonorejo mangrove area is a mangrove forest area that has innovated into an ecotourism area, resulting in a lot of garbage found in the mangrove forest area from visitors. Inorganic waste is waste produced from non-biological materials in the form of synthetic products or the result of technological processes for managing mining materials or natural resources and cannot be decomposed by nature, for example plastic. Mangrove vegetation at the seedling level is rejuvenation from sprouts to a height of 1.5 m. The objectives of the study were to identify the density of inorganic waste in the mangrove vegetation at the seedling level, to analyze the density of the vegetation at the seedling level, to analyze the impact of inorganic waste on the growth of the vegetation at the seedling level. The method used to measure the density of mangroves and waste density using Line Plot Transects. The most waste found was 46 plastic bottles, and other inorganic waste found was styrofoam, and the density of seedlings was 2200 seedlings/ha. The relationship between waste density and seedling density showed (R²) of 0.8399 which indicated that the negative correlation was the more waste, the less seedlings. The impact caused by inorganic waste can threaten mangrove plants, especially at the seedling level and the life of the biota in the ecosystem.